(untitled) (REMUNOM, 2026)
This article analyzes the importance of field activities and events held in 2025 with students of the Agronomy course at UERGS, Vacaria/RS campus. In total, sixteen field trips and eight events were developed, highlighting the diversity of formative strategies adopted. These actions proved fundamental for the students’ comprehensive training, promoting the articulation between theory and practice, contact with different productive realities, and an understanding of the technical, environmental, and socioeconomic challenges of the agricultural sector.